Effectiveness of talent management to improving organisational performance in government owned bank - Nasir, Yong Salmah; Mohtar, Shahimi; Ariffin, Ahmad Shabudin (Akademia Baru, 2017)
This research was carried out using method of questionnaire among officer in Malaysian Government own Bank. Talent management is the main purpose of the study to examine the effect on organizational performance. Talent management is considered as the strategy of organization performance and involves activities such as attracting, retention, development, motivation and succession planning. All the activity needed in order for success and improve performance. To ensure organizational succeed in highly competitive market, the organization must have the right employees at the right job. It is additional benefits for an organization and for employees to identify and develop by talent management strategy and give the impact to organizational performance.